The Role of TRESK in Discrete Sensory Neuron Populations and Somatosensory Processing - Weir, Greg A.; Pettingill, Philippa; Wu, Yukyee; Duggal, Galbha; Ilie, Andrei-Sorin; Akerman, Colin J.; Cader, M. Zameel (Frontiers in Molecular Neuroscience, 2019)
Two-pore domain K+ (K2P) channels generate K+ leak current, which serves a vital role in controlling and modulating neuronal excitability. This diverse family of K+ channels exhibit distinct expression and function across neuronal tissues. TWIK-related spinal cord K+ channel (TRESK) is a K2P channel with a particularly enriched role in sensory neurons and in vivo pain pathways. Here, we explored the role of TRESK across molecularly distinct sensory neuron populations and assessed its contribution to different sensory modalities. We found TRESK mRNA only in select populations of C- and A-δ nociceptors, in addition to low threshold D-hair afferents. Neurons from mice in which TRESK has been ablated demonstrated marked hyperexcitability, which was amplified under inflammatory challenge. Detailed behavioural phenotyping of TRESK knockout mice revealed specific deficits in somatosensory processing of noxious and non-noxious stimuli. These results demonstrate novel roles of TRESK in somatosensory processing and offer important information to those wishing to target the channel for therapeutic means.